2021
DOI: 10.3390/cryst11040403
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Sidewall Passivation Technology on the Optical Performance for Smaller Size GaN-Based Micro-LEDs

Abstract: Micro-light emitting diodes (Micro-LEDs) based on III-nitride semiconductors have become a research hotspot in the field of high-resolution display due to its unique advantages. However, the edge effect caused by inductively coupled plasma (ICP) dry etching in Micro-LEDs become significant with respect to the decreased chip size, resulting in a great reduction in device performance. In this article, sector-shaped GaN-based blue Micro-LEDs are designed and fabricated. Additionally, the device performance of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Using this approach, ultra-small µLEDs could be demonstrated with dimensions of 10 µm or less [9][10][11]. However, the mesa etching process usually introduces surface damage at the sidewalls of InGaN QWs, which causes more non-radiative surface recombination and reduces the external quantum efficiency (EQE) of µLEDs [12,13]. This effect becomes significant, especially when the dimension of the µLEDs shrinks [14].…”
mentioning
confidence: 99%
“…Using this approach, ultra-small µLEDs could be demonstrated with dimensions of 10 µm or less [9][10][11]. However, the mesa etching process usually introduces surface damage at the sidewalls of InGaN QWs, which causes more non-radiative surface recombination and reduces the external quantum efficiency (EQE) of µLEDs [12,13]. This effect becomes significant, especially when the dimension of the µLEDs shrinks [14].…”
mentioning
confidence: 99%
“…For the GaN material system, the 𝐴, 𝐵, and 𝐶 coefficients were found to depend on the size of MicroLED and peak emission wavelength (𝜆 𝑝 ) according to the equations ( 19)-( 22) above. These empirical equations were based on data [7][8][9][10][11][12].…”
Section: 𝐿𝐸𝐸 = 𝜂 𝑡 + 𝜂 𝑠 + 𝜂 𝑠𝑡 + 𝜂 𝑡𝑠mentioning
confidence: 99%
“…To achieve effective light extraction, several researches have reported that the inclined mesa sidewall of UV LEDs could extract the strong TM-polarized in-plane emission in an the micro-LEDs are formed by dry etching. Several techniques such as wet chemical treatment have been employed to minimize the sidewall effects in GaN based micro-LEDs [42,43]. Chee et al have reported that using post-processing methods based on HCl followed by KOH chemical treatment could recondition the sidewall damage, improving the LEE of (in their case) photonic crystal AlGaN UVC LEDs [44].…”
Section: B Techniques For Improving Uv Micro-led Efficiencymentioning
confidence: 99%